Implementation of Equality Education Program Policy at SPNF SKB Kaidipang, Bolaang Mongondow Utara Regency - Masrifa Wengkeng; Lisda Van Gobel; Tety Thalib (Formosa Journal of Applied Sciences, 2022)
This study aims to determine the implementation of the Equality Education Program in the Non-Formal Education Unit, Learning Activities Studio (SPNF SKB) Kaidipang, North Bolaang Mongondow Regency. From the results of the study, there are still several obstacles including: Communication that is still not well established between the government, identification officers and the community, then inadequate Human Resources, especially from educational backgrounds who still do not have a Diploma in Out of School Education, not to mention Facilities and Infrastructure The available resources have not met the needs, especially in the teaching and learning process and the bureaucracy. It is recommended that if there is a communication gap in an organization, an evaluation is immediately carried out, then it is necessary to hold training for officers in order to create good human resources, the availability of facilities and infrastructure in an organization must be adequate because it strongly supports the success of the programs that have been set. , and to achieve something that has been jointly determined, an orderly bureaucracy is needed. The Non-Formal Education Unit, Learning Activity Center (SPNF SKB) KAIdipang continues to strive to continue to improve good service to the community, foster community trust.